2020
DOI: 10.1080/16549716.2019.1684072
|View full text |Cite
|
Sign up to set email alerts
|

Ad hoc interpreters in South African psychiatric services: service provider perspectives

Abstract: Background: Language and communication lie at the heart of good quality mental health care and are a vital, yet complex, part of the diagnostic and treatment process. In South African mental health care, ad hoc interpreting arrangements are the status quo. However, these can cause both clinician and patient shame and distress. Objective: Though this issue has been researched from the point of view of informal interpreters, relatively little is known about psychiatrists' experiences of working with ad hoc inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…14,16 It is common practice in the South African healthcare sector to use untrained bi-or multilingual staff and ad hoc interpreters. 20 Despite not being the first choice, ad hoc interpreters (e.g. family or friends) have some benefits and may often be the only option available in the facility (Table 1).…”
Section: What Are the Types Of Medical Interpreters?mentioning
confidence: 99%
See 1 more Smart Citation
“…14,16 It is common practice in the South African healthcare sector to use untrained bi-or multilingual staff and ad hoc interpreters. 20 Despite not being the first choice, ad hoc interpreters (e.g. family or friends) have some benefits and may often be the only option available in the facility (Table 1).…”
Section: What Are the Types Of Medical Interpreters?mentioning
confidence: 99%
“…Ad hoc interpreters in local studies were found to have inadequate language proficiency and were prone to frequent errors during interpretation. 5,19,20 Most published data on this topic comes from the Western Cape Province and isiXhosa-speaking patients. 5 Thus, a research gap exists regarding other provinces and languages in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The struggle itself is both broader and more complex. Added to this are the layers of taken-for-granted workplace relationships (themselves, as always, relationships of both enablement and exclusion, always in an unequal power matrix) which may constrain change and which always have to be understood in the context of the local vulnerabilities of all actors in a work environment (Hagan et al, 2020). Given all of these considerations, we do not claim that our insights lead to immediately implementable lessons for change, but we suggest that having discussions such as those we are engaged in, on a large scale, may play some role in the slow business of social change.…”
Section: Conclusion: a Decolonial Understanding And The Complexity Of...mentioning
confidence: 99%
“…The struggle itself is both broader and more complex. Added to this are the layers of taken-for-granted workplace relationships (themselves, as always, relationships of both enablement and exclusion, always in an unequal power matrix) which may constrain change and which always have to be understood in the context of the local vulnerabilities of all actors in a work environment (Hagan et al, 2020).…”
Section: Conclusion: a Decolonial Understanding And The Complexity Of...mentioning
confidence: 99%
“…Damit widerspricht diese Studie vielen anderen Arbeiten und Expertenmeinungen, die nicht zuletzt auch wegen der variierenden medizinischen Standards in den Herkunftsländern, der Anstrengungen auf der Flucht und der Hygienezustände in vielen Gemeinschaftsunterkünften eine höhere Prävalenz bestimmter Infektionskrankheiten unter den Geflüchteten vermuten (Hampel et al 2016). Dies lässt sich auch exemplarisch an einer Studie zur Seroprävalenz für Hepatitis B bei Geflüchteten zeigen: Hier lag die Prävalenz für das HBsAg, einem wichtigen serologischen Marker einer durchgemachten Hepatitis-B-Virusinfektion, bei 2,3% und damit deutlich höher als in der deutschen Allgemeinbevölkerung (Hampel et al 2016) (Hagan et al 2020).…”
Section: Beratungsanlässe Von Geflüchtetenunclassified